(untitled) (Scientific journal of the Fergana State University, 2024)
This article explores metonymic modeling in business discourse, examining how metonymy functions to streamline, convey, and influence communication within various business contexts. By analyzing a diverse corpus of business-related texts, including corporate communications, financial reports, and marketing materials, the study identifies key metonymic expressions and categorizes their functions. The findings reveal that metonymy enhances communication efficiency by simplifying complex concepts, facilitates branding and corporate identity through symbolic representations, and aids in the clear discussion of financial phenomena. Sector-specific variations in metonymic usage highlight how different industries leverage metonymy to meet their unique communication needs. The study underscores the significance of metonymy in creating shared understandings and shaping perceptions within the business environment. It also suggests areas for future research, including broader and more quantitative analyses, and the exploration of metonymy’s interplay with other linguistic devices. Overall, this article provides valuable insights into the role of metonymy as a cognitive and communicative tool in business discourse, offering implications for improving communication strategies and understanding organizational dynamics.